Contrabando de agrotóxicos no Brasil: O perigo é real?uma análise com base em laudos periciais de produtos apreendidos (2008-2018) - Rodrigo Fracalossi de Moraes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Between 2007 and 2018, federal agencies in Brazil confiscated around 1,300 cargoes of smuggled or counterfeit pesticides. These products are often described by industry bodies as more toxic than those legally traded or as ineffective against pests, but there is little information about this type of crime. This article presents a profile of this type of crime in Brazil, based on a dataset with 3,690 observations, drawn from information about confiscated pesticides in forensic reports from the Brazilian Federal Police. Based on evidence from this dataset, this article concludes that: the volume of pesticide smuggling is probably small when compared to the volume of pesticides consumed in Brazil; there is no evidence that smuggled products are more toxic than those traded in the legal market, although they may be of greater environmental risk; smuggled goods are rarely counterfeit; smuggling is caused by price differences rather than bans on the use of certain active ingredients; pesticides in unlabelled packings are more toxic than those in labelled packings; the main origin of smuggled pesticides is China, which commonly enter into Brazil through Paraguay and Uruguay; confiscations tend to grow in periods of pre-planting or planting; there is some evidence that organized groups are involved with this type of crime, but it is mainly conducted by petty smugglers. In summary, evidence indicates that pesticide smuggling does not bring substantial additional risks to public health, occupational health or the environment, besides those already observed in products bought in the legal pesticide market. Although smuggling must be repressed, this topic may be mainly of symbolic importance. In a context in which various actors within and outside the state mobilize in favour of greater restrictions on pesticides and higher levels of taxation on this sector, emphasising the potential negative consequences of smuggling contributes to associate the sector to a responsible behaviour and to expand their networks with government officials.
Keywords: K42; Q17; 330; pesticides; smuggling; Brazil; public health; environment; special interest groups